Family-friendly benefits, organizational culture, and applicant attraction - Baranczyk, Michele Chapin, author; Johnson, Stefanie K., advisor (Colorado State University. Libraries, 2009)
In this study, family-friendly organizational benefits and family-friendly culture are examined with regard to applicant attraction. A pilot study helped determine the perceived monetary value of organizational benefits by potential employees. For the main study, two samples were obtained: a college student sample with 291 participants and a current job-seeker sample with 152 participants. Participants were assigned to view 1 of 4 job advertisements, comprised of high or low family-friendly benefits, and high or low family-friendly culture. Analysis of Variances (ANOVAs) results indicated no main effects of family-friendly benefits or cultures. However, significant effects were detected when adding sex and future family intentions into the analysis using 3-way ANOVAs. Results indicate sex differences between males and females in both the student and current job-seeking sample. Implications and future research are discussed.
Keywords: benefits; employee benefits; family-friendly policies; organizational culture; recruitment; studies; gender differences; attitudes